Environmental ethics - Fisso, Maria Beatrice; Sgreccia, Elio (Medicina e Morale, 1996)
This is first part of what is to be the introduction of a bibliographycal collection with comments, regarding some questions on environmental ethics. The authors first point out the stages during which the evolution of civilization has been conditioned by the relationship between man and the environment: primitive, pastoral, industrial and technological civilizations, or the nuclear or space civilization, also called the civilization of the genetic revolution. It is then shown how, starting from the second part of the seventies, nature has progressively been given greater importance. It is no longer considered a matter simply to be studied by science, but is seen as worthy of ethical reflection and in fact from this moment environmental ethics have acquired the strength of an institutional discipline. Nevertheless over the last fifteen years the philosophical debate on these questions has mainly developed in English speaking countries, while in Italy it is still at an initial phase. Classical philosophical thought has always been formulated in a very anthropocentric way but during the seventies some philosophers attempted to change this approach and propose a less anthropocentric or even an ecocentric vision. After an accurate examination of these various currents of thought the authors conclude the first part of their article by rejecting both the extremists of ecophilosophies and the opinion of those who believe in the unlimited possibility of exploiting nature. In fact the new scientific and cultural acquisitions make it necessary to reconsider the relationship between man and nature in order to establish ethical principles which can originate human behaviour in this area.